Post-harvest processing in medicinal turmeric - Thounaojam, A S; Chaudhary, R I; Patel, K V; Solanki, R U; Chavda, N K (Indian Horticulture, 2023)
India is the major turmeric exporter and represents 80% of the global production with the net profit of 201.2 million USD during 2020. Turmeric has high potential and enormous demand at international market with the global market value of 4419 million USD in 2023. The small and marginal farmers of turmeric growers could earn more revenue by adopting a small and simple post-harvest processingtechnique like curing rather than simply selling the fresh turmeric rhizome in market. This will not only impact the socio-economic status of such group of farmers, but it will also make a strong bonding between the growers and the consumers or companies directly, and also eventually fasten the process to bring the product in foreign market without compromising the quality and quantity. So,curing is a very significant post-harvest step, which involves boiling of rhizomes and drying to maximize the profit to the growers.